The effect of training method and strength of the hands muscle towards float serve in volleyball extracurricular - Bethi Novianingsih; Djoko Pekik Irianto (Kazimierz Wielki University, 2019)
Aim: The aim of the research is to find out: 1) the different of training method influence towards volley ball float serve skills on male students of volleyball extracurricular in Bantul 1 senior high school, Bantul 2 senior high school and Bambanglipuro 1 senior high school; 2) the different of strenght of the hands muscle influence towards volley ball float serve skill on male students of volleyball extracurricular in Bantul 1 senior high school, Bantul 2 senior high school and Bambanglipuro 1 senior high school; 3) Strenght of the hands muscle and training method interactions towards volleyball float serve skill on male students of volleyball extracurricular in Bantul 1 senior high school, Bantul 2 senior high school and Bambanglipuro 1 senior high school. Methods: This research is an experimental research with 2x2 factorial designs, using pretest and posttest. Sample which used in this research is total of 40, divided into 2 groups of high and low depends on the test result from attributive variable (high group 20 and low group 20). Instrument measurement for strength of the muscle hands using pull and push dynamometer, with the score of validity of 0.63 and the score of reliability of 0.63. Service float skill measurements using AAHPER serving accuracy test, with the test validity score of 0.920 and the score of reliability of 0.690. Technique for data analysis used in this research is normality test using kolmogorov smirnov test, homogeneity test variant using levene's test and hypothesis research test using two way anova analysis. Results: The result of the research is: 1) the result of two way anova analysis on training method obtained the f score of 4.381 with significance score of 0.043; 2) the result of two way anova analysis on strength of muscle hands variable obtained F score of 9.038 with the significance score of 0.005; 3) the result of Two Way Anova analysis on interaction approach with hand eye coordination data obtained the F score of 13.625 with the significance score of 0.001. Conclusion: The conclution for this research is: 1) There is a significant influence from training method towards volley ball float serve skill on male students who join volleyball extracurricular in Bantul 1 senior high school, Bantul 2 senior high school and Bambanglipuro 1 senior high school; 2) There is a significant influence from strength of hands muscle towards volley ball float serve skill on male students who join volleyball extracurricular in Bantul 1 senior high school, Bantul 2 senior high school and Bambanglipuro 1 senior high school; 3) There is a significant interaction between training method and strenght of hands muscle towards volleyball float serve skill on male students who join volley ball extracurricular in Bantul 1 senior high school, Bantul 2 senior high school and Bambanglipuro 1 senior high school.